Content Analysis on Twitter Users Interaction within First 100 Days of Jakarta’s New Government by Using Text Mining - Maarif, Muhammad Rifqi (Jurnal Pekommas, 2018)
As one of the biggest democratic country in the world, Indonesia have very responsive society towards the various political move in either the central or local governments. In Indonesia, the first 100 days of new government era usually became a crucial timelines in which the society give their intents attention to government’s performance. By the massive penetration of online social networking platform likes Twitter, the interaction between netizens and government figure official account will significantly increase. The povincial election for of Jakarta momentum was one of the most attractive political events in which Anies Baswedan and Sandiaga Uno were elected the lead of Jakarta government. The implication is the society would look intensively at their performance within their first 100 days. With the huge amount of Twitter users in Indonesia, Indonesian Twitter was very reactive towards any movement of Anies Sandi. Thus, this platform can be utilized to monitor the public opinion towards first 100 days of Anies Sandi government. In this study, we analyzed the content of conversations in interaction among the netizen and official Twitter Account of Anies Baswedan (@aniesbaswedan), Sandiaga Uno (@sandiuno) and the Government of Jakarta (@DKIJakarta). A set of text mining techniques was employed in this study.